High-Intensity Interval Training Increases Osteoarthritis-Associated Pain-Sensitive Threshold Through Reduction of Perineuronal Nets of the Medial Prefrontal Cortex in Rats - Zhang, X; Kong, F E; Lin, C-S; Ye, Z-Q; Chen, A-L; Cheng, K; Li, X-P (Physiological research, 2024)
High-intensity interval training (HIIT) is considered an effective therapy strategy for improving chronic pain associated with osteoarthritis (OA). Perineuronal nets (PNNs) are specialized extracellular matrix structures in the cerebral cortex that play a crucial role in regulating chronic pain. However, little is unknown whether HIIT could alleviate OA pain sensitization by reducing PNN levels. This study aimed to determine whether HIIT could reduce sensitivity of the affected joint(s) to pain in a chronic pain model in rats with OA. A rat model of interest was induced by intra-articular injection of monosodium iodoacetate (MIA) into the right knee. Thereafter, the mechanical withdrawal thresholds (MWTs) and PNN levels in the contralateral medial prefrontal cortex (mPFC) were measured in rats in the presence or absence of HIIT alone or in combination with injection of chondroitinase-ABC (ChABC) into the contralateral mPFC (inducing the degradation of PNNs), respectively. Results indicated that rats with OA exhibited significant reductions in MWTs, but a significant increase in the PNN levels; that HIIT reversed changes in MWTs and PNN levels in rats with OA, and that pretreatment of ChABC abolished effects of HIIT on MWTs, with PNN levels not changed. We concluded that pain sensitization in rats with OA may correlate with an increase in PNN levels in the mPFC, and that HIIT may increases OA pain-sensitive threshold by reduction of the PNN levels in the mPFC. Keywords: Osteoarthritis, Chronic pain, Pain sensitization, High-intensity interval training, Perineuronal nets.
Keywords: Prefrontal Cortex; Male; Physical Conditioning, Animal; osteoartróza; potkani Sprague-Dawley; Nerve Net; práh bolesti; prefrontální mozková kůra; kondiční příprava zvířat; mužské pohlaví; Osteoarthritis; krysa rodu Rattus; Animals; zvířata; nervová síť; Rats; High-Intensity Interval Training; Pain Threshold; Rats, Sprague-Dawley; vysoce intenzivní intervalový trénink